Literature Review: Pengaruh Penggunaan Media Sosial Instagram Sebagai Media Edukasi Gizi: Literature Review: Effects of Using Instagram Social Media as a Nutrition Education Media - Deri Andika Putra; Suminah -; Eti Poncorini Pamungkasari (Universitas Airlangga, 2022)
Background: Nutrition is one thing that is important and very needed by the body. Indonesia has various kinds of social media that several users often play. One social media that has quite a lot of users is Instagram. During this pandemic, knowledge can come from anywhere. They are starting from teachers, friends, webinars, and so on. This knowledge sharing can be done by utilizing various applications such as Zoom, Google Meetings, etc. In addition, social media applications such as Instagram can provide users with various information and knowledge. Objectives: The purpose of writing this article is to analyze the influence of using social media, Instagram, for nutrition education. Discussions: This type of article is written using qualitative research using literature studies. This study uses searches on the Google search website, Google Scholar, and Research Gate with the keywords